Description of Elderly Mental Status in Work Area Puskesmas Pampang Makassar - Ayu Wulandari; Yuliana Syam; Arnis Puspitha (Faculty of Nursing, Universitas Hasanuddin, 2018)
Introduction:mental status of elderly is an emotional or cognitive state in the elderly is shown by the behavior of the stand. Mental health problems are very important for the elderly and often occurs in the elderly. The incidence of mental disorders in the elderly status is very high. paired mental status in elderly pose a variety of problems that can affect physical health, psychological, social and quality of life of the elderly so that the necessary nursing services for the early detection of mental status disorders that occur among the elderly. Method: The study design quantitative descriptive survey method. Samples numbered 97 people were selected using cluster random sampling. Primary data was collected by questionnaire the Mini Mental Status Examination (MMSE). Result:T he study of 97 respondents showed that 55.7% had normal mental status, impaired mental status light there are 29.9% and 14.4% of elderly with impaired mental status severe. Based propporsi elderly who suffer from mental status of the most widely experienced by women (52.4%), greater in very old age (100%), greater in elderly unmarried (100%), greater in elderly are not in school ( 70.6%), greater in elderly with a history of self-employed work (44.7%), and greater in the elderly with a history of rheumatic disease (61.1%). Conclusions: Mental status of elderly in Puskesmas Kota Makassar Pampang mostly normal. Therefore, elderly mental health need to be detected early to avoid the impact of mental disorders in the elderly.